Toriko. Collection 02, episodes 27-50 [videorecording (DVD)] - Shimabukuro, Mitsutoshi, 1975- (FUNimation Productions, Ltd., 2014)
"Toriko, Komatsu, and a host of hopeful heroes bundle up and begin the treacherous trek into the chilling confines of Ice Hell! The prize that awaits them, Century Soup, is among the rarest of gourmet treasures - and the most divine delicacy ever to grace a bowl and a spoon"--Container.